Acidification of intracellular pH in MM tumor cells overcomes resistance to hypoxia-mediated apoptosis in vitro and in vivo - Gastelum, Gilberto; Kraut, Jeffry; Veena, Mysore; Baibussinov, Alisher; Lamb, Christopher; Lyons, Kylee; Chang, Eric Y.; Frost, Patrick (Frontiers in Oncology, 2023)
Multiple myeloma (MM) is an incurable cancer arising from malignant plasma cells that engraft in the bone marrow (BM). While currently incurable, it is more than likely that the tumor microenvironment (TME) plays a critical role in MM development and this includes relatively poorly investigated physical parameters of the BM, like hypoxia and pH. In this study we explore the effects of pH resulting from hypoxia-mediated anaerobic or aerobic glycolysis on the TME and its critical role in maintenance of the intracellular pH within obligate physiological levels. We show that hypoxia-mediated apoptosis of MM cells is correlated with acidic intracellular pH (less than ~6.6) in vitro. Furthermore, the ability of MM cells to regulate pH is dependent on HIF activity and this was inhibited by inhibitors a polyamide HIF responsive element binding compound (HIF-PA), a carbonic anhydrase inhibitor (acetazolamide), and an NHE-1 inhibitor (amiloride). In contrast, treatment of cells with an alkalization agent, Na-lactate, rescued these cells from hypoxia-mediated killing by increasing the intracellular pH. Using a murine xenograft model of MM, we used PET/CT to study the effects of tumor growth and development on hypoxia and found that acetazolamide decreased cell growth in the tumor nodules. While targeting hypoxia and HIF have long been proposed as an anti-tumor therapy, the clinical efficacy of such strategies has been modest. However, targeting intracellular pH may be more effective at treating cancers within a hypoxic TME.